African-American and white inequality in the American South: evidence from the 19th Century Missouri state prison - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2007)
The use of height data to measure living standards is now a well-established method in economic history. Moreover, a number of core findings in the literature are widely agreed upon. There are still some populations, places, and times, however, for which anthropometric evidence remains thin. One example is 19th century African-Americans in US border states. This paper introduces a new data set from the Missouri state prison to track black and white male heights from 1829 to 1913. Where modern blacks and whites come to comparable terminal statures when brought to maturity under optimal conditions, whites were persistently taller than blacks in this Missouri prison sample. Over time, black and white adult statures remained approximately constant throughout the 19th century, while black youth stature increased considerably during the antebellum period and decreased during Reconstruction.
Keywords: N31; J15; J70; I12; I31; 330; Lebensstandard; Gesundheit; Schätzung; USA (Südstaaten)